Automasi Dokumentasi Aset Melalui Mekanisme Dynamic Report Generation dengan Transformasi Visual secara Real-Time - Madya, Akbar (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2026)
Facilities and infrastructure management often have difficulty synchronizing data administration with visual documentation. This research develops an Android-based MySarPras application with SQLite architecture and integration of iText7 library and Apache POI. The novelty of this research lies in the visual transformation flow mechanism that optimizes memory management through downsampling techniques to produce PDF/Excel reports proportionally. The results of the Black Box test show that all CRUD functions run stably with a high level of interoperability through the Implicit Intent feature. The results of the performance test showed that the system was able to generate reports instantly with a duration of 1.8 seconds for 10 data to 9.3 seconds for 100 data assets with a file size of up to 30.3 MB. MySarPras has succeeded in digitizing the data collection process to be more accountable and efficient without internet dependence. The use of mobile technology offers a potential alternative means to efficiently address the bureaucratic needs of asset management in various organizations.